Clinical, neurocognitive and demographic factors associated with functional impairment in the Australian Brain and Mind Youth Cohort Study (2008–2016). Issue 12 (18th December 2018) - Lee, Rico S C; Hermens, Daniel F; Naismith, Sharon L; Kaur, Manreena; Guastella, Adam J; Glozier, Nick; Scott, Jan; Scott, Elizabeth M; Hickie, Ian B
Abstract : Objectives: We sought to determine the unique and shared contributions of clinical, neurocognitive and demographic factors to functional impairment in a large, transdiagnostic, clinical cohort of adolescents and young adults. Design: Cross-sectional baseline data from a prospective, cohort study. Setting: Help-seeking youth referred from outpatient services were recruited to the Brain and Mind Youth Cohort (2008–2016) in Sydney, Australia. Participants: In total, 1003 outpatients were recruited, aged between 12 and 36 years (mean= 20.4 years, 54% female), with baseline diagnoses of affective, psychotic, developmental or behavioural disorders. Interventions: Treatment as usual. Primary outcome measures: Social and occupational functioning was used to index level of functional impairment. Structural equation modelling was used to examine associations between neurocognition, core clinical symptoms and alcohol and substance use, and clinician-rated and researcher-rated functional impairment. Moderator analyses were conducted to determine the potential influence of demographic and clinical factors (eg, medication exposure). Results: Independent of diagnosis, we found that neurocognitive impairments, and depressive, anxiety and negative symptoms, were significantly associated with functioning. The association of neurocognition with social and occupational functioning remained significant even when constraining for age (15–25-year-olds only) or diagnosis (affective disorders only) in the final model. Conclusions: This study demonstrated that, in a clinically representative sample of youth, the key determinants of functioning may not be disorder specific. Further, evidence of neurocognitive dysfunction suggests that interventions that target cognition and functioning should not necessarily be reserved just for older adults with established illness.